Advances in High-Speed Structured Illumination Microscopy - Zhao, Tianyu; Wang, Zhaojun; Chen, Tongsheng; Lei, Ming; Yao, Baoli; Bianco, Piero R. (Frontiers in Physics, 2021)
Super-resolution microscopy surpasses the diffraction limit to enable the observation of the fine details in sub-cellular structures and their dynamics in diverse biological processes within living cells. Structured illumination microscopy (SIM) uses a relatively low illumination power compared with other super-resolution methods and has great potential for meeting the requirements of live-cell imaging. However, the imaging acquisition and reconstruction speeds limit its further applications. Here we review several methods designed to improve the speed of SIM and discuss their application in live-cell imaging.